Constructal design for convection melting of a phase change body. (August 2016) - Ziaei, S.; Lorente, S.; Bejan, A.
Highlights: Time-dependent melting with natural convection in a cylinder. Architectures selected for fast melting: single lines, and tree shaped. The heat transfer density increases as the complexity of the heater increases. The angles between heater branches have a minor effect. Abstract: This paper documents a numerical study of time-dependent melting dominated by natural convection in a cylinder filled with a phase change material. In accord with constructal design, the search is for effective heat-flow architectures. The volume-constrained improvement of the designs for heat flow begins with assuming the simplest structure, where a single line serves as heat source. Next, the heat source is endowed with freedom to change its shape as it grows. The objective of the numerical simulations is to discover the geometric features that lead to the fastest melting process. The results show that the heat transfer rate density increases as the complexity and number of degrees of freedom of the structure are increased. Furthermore, the angles between heat invasion lines have a minor effect on the global performance compared to other degrees of freedom: number of branching levels, stem length, and branch lengths. The effect of natural convection in the melt zone is documented.